2020
DOI: 10.3389/fpsyt.2020.608154
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic Characterization of Resting State Connectivity Abnormalities in Schizophrenia Patients

Abstract: Background: Patients with schizophrenia show abnormal spontaneous oscillatory activity in scalp-level electroencephalographic (EEG) responses across multiple frequency bands. While oscillations play an essential role in the transmission of information across neural networks, few studies have assessed the frequency-specific dynamics across cortical source networks at rest. Identification of the neural sources and their dynamic interactions may improve our understanding of core pathophysiologic abnormalities ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The observation of increased resting-state gamma-band oscillations (RS-GBO) under the influence of ketamine parallels observations made in patients with schizophrenia ( 11 13 , 61 ). As elaborated in the introduction, the generation of GBO involves a neural microcircuit consisting of pyramidal cells, fast-spiking inhibitory GABA-releasing PV + -interneurons ( 23 ), and SST + -interneurons ( 28 ).…”
Section: Discussionsupporting
confidence: 73%
“…The observation of increased resting-state gamma-band oscillations (RS-GBO) under the influence of ketamine parallels observations made in patients with schizophrenia ( 11 13 , 61 ). As elaborated in the introduction, the generation of GBO involves a neural microcircuit consisting of pyramidal cells, fast-spiking inhibitory GABA-releasing PV + -interneurons ( 23 ), and SST + -interneurons ( 28 ).…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, we observed that both the LORD and EROD groups together had increased ReHo in the left rolandic operculum gyrus/left superior temporal gyrus compared to HCs. The rolandic operculum gyrus and superior temporal gyrus belong to the auditory network ( Oh et al, 2018 ; Koshiyama et al, 2020 ), which has the function of integrating auditory stimuli and processing them, and is closely related to human emotions ( Phillips et al, 2001 ; Wang et al, 2019 ). Previous studies have found that depression scale scores are positively correlated with gray matter in the left rolandic operculum gyrus and left superior temporal gyrus, suggesting that these two brain regions also play a role in mood regulation ( Besteher et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects EEG recordings from an archival cohort of 147 healthy comparison subjects and 158 schizophrenia patients, where resting-state frequency effects and connectivity analyses were previously described, 44,45 were obtained for the present analyses. Since the groups differed in age and sex, subsamples of 128 healthy comparison subjects and 142 schizophrenia patients matched on age and sex were used.…”
Section: Methodsmentioning
confidence: 99%
“…43 Our prior studies showed that (i) resting-state gamma-band EEG power at the frontal and temporal scalp electrodes is increased in schizophrenia patients relative to healthy subjects 44 ; and (ii) that significantly increased directed connectivities in the gamma band are observed between estimated frontal and temporal source regions in schizophrenia patients relative to healthy subjects. 45 However, the underlying neural mechanisms of abnormal higher gamma-band EEG activity in schizophrenia patients remains unclear. 44,[46][47][48][49] Identification of the contributing lower frequently neural synchronization such as delta-and theta-band EEG to gamma-band EEG power abnormality at rest (i.e.…”
mentioning
confidence: 99%